Pengaruh Penduduk Usia Produktif, Investasi, dan Pertumbuhan Ekonomi Terhadap Pendapatan Asli Daerah di Provinsi Jambi - Atep Trendi Rohman Hidayat (Universitas Batanghari Jambi, 2020)
This study aims to test and analyze; 1) The effect of the productive age population on the original income of the region in Jambi Province in 2003-2018; 2) the effect of investment on regional original income in the province of Jambi in 2003-2018; 3) the effect of economic growth on regional original income in Jambi Province in 2003-2018. This research is a confirmatory study. Data collection using documentation techniques sourced from the central statistical body (BPS), the data in this study are secondary. The data used in the form of time series data from 2003-2018 the data analysis technique used is multiple linear regression The results of data analysis show that: 1) the productive age population is negatively related and insignificant to the original regional income in the province of Jambi in 2003-2018; 2) investment is positively and significantly related to regional original income in Jambi province 2003-2018; 3) economic growth is negatively and significantly related to regional original income in Jambi province in 2003-2018.